Reinventing Effective Grounding Systems via Optimal Soil Composition, Thickness, and Replacement Parameters Under Fault Conditions - Ahmed El-Tayeb Khalil; Adel Zein El Dein; Mahmoud Ramadan Hefny; Matti Lehtonen; Mohamed M. F. Darwish (IEEE Access)
This paper investigates the impact of soil replacement around a ground grid on its performance, with a focus on replacing the base soil with a lower-resistivity material and analyzing the influence of the replaced layer’s area and thickness. The study explores the effects of soil replacement on critical parameters such as total ground resistance, earth surface potential (ESP), current density, and electric field distribution under line-to-ground fault conditions. Key soil properties, including water content, thermal and electrical conductivity, heat capacity, density, and relative permittivity coefficient, are also considered to assess their role in optimizing the grounding environment. Despite extensive research on grounding system performance, most existing studies have assumed homogenous soil models or ideal conditions, overlooking the complex variations in real soil properties and environmental factors that critically affect fault performance. Traditional design methodologies often fail to address the effects of non-uniform soil composition, moisture variations, and localized resistivity changes, leading to suboptimal safety and performance in practical installations. This gap necessitated the proposed research, which systematically investigates soil replacement strategies as a practical and scalable solution to enhance grounding system efficiency under realistic conditions. This paper addresses a detailed investigation of how targeted soil replacement strategies influence grounding system behavior under realistic fault conditions. It introduces a practical framework that integrates both environmental and electrical soil properties to enhance performance evaluation and design accuracy. The results demonstrate that replacing high-resistivity sand with low-resistivity clay significantly reduces total ground resistance. For a 1-meter-thick replaced layer, resistance decreased from $8.4~Ω $ to $3.17~Ω $ (a 62.3% reduction) when sand was replaced with clay, whereas replacing clay with sand increased resistance to $11.5~Ω $ (a 37% increase) at 1.5 meters of thickness. Similarly, ESP values dropped substantially when clay was introduced as a replacement layer, enhancing current dissipation and reducing surface potential risks. Moreover, expanding the replaced soil width from 25 meters to 50 meters resulted in further ground resistance reduction, with values decreasing from $3.3~Ω $ to $3.17~Ω $ when replacing sand with clay, while resistance increased from $2.5~Ω $ to $8.4~Ω $ when replacing clay with sand. The study also revealed that a 50% replacement of sand with clay improved current density uniformity and enhanced grounding efficiency compared to full replacement scenarios. The findings show that replacing the covered soil layer achieves greater improvements in reducing ground resistance and enhancing current dissipation compared to the base layer. Increasing the thickness and area of the replaced soil further improves current density uniformity, reduces surface potential, and significantly boosts the safety and efficiency of grounding systems, especially in high-resistivity soils.INDEX TERMS Lightning strokes, grounding systems, soil resistivity, fault current dissipation, earth surface potential, simulation analysis.